2021
DOI: 10.3390/nu13072221
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Iron Status in Pregnancy and Child Health Outcomes after Birth: A Systematic Review and Meta-Analysis

Abstract: In pregnancy, iron deficiency and iron overload increase the risk for adverse pregnancy outcomes, but the effects of maternal iron status on long-term child health are poorly understood. The aim of the study was to systematically review and analyze the literature on maternal iron status in pregnancy and long-term outcomes in the offspring after birth. We report a systematic review on maternal iron status during pregnancy in relation to child health outcomes after birth, from database inception until 21 Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 77 publications
(152 reference statements)
1
37
0
1
Order By: Relevance
“…Despite the low prevalence of homozygosis for HFE gene mutations in our study population (only 4.8% for H63D genotype), the prevalence of having any HFE gene mutation is around 46% in the Mediterranean population [ 34 , 60 ], which turn it into an important risk factor to consider when prescribing iron supplementation. There are some indications from observational studies that not only iron deficiency but also iron excess negatively affects the child’s neurodevelopment [ 18 , 32 , 33 , 35 , 36 ] and, based on that, some main researchers in this field have proposed to adapt the prenatal iron supplementation to the individual’s requirements to mitigate the potential damage from any maternal iron imbalance [ 22 , 23 , 25 , 41 ]. However, few studies have tested this hypothesis, obtaining inconsistent results [ 37 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the low prevalence of homozygosis for HFE gene mutations in our study population (only 4.8% for H63D genotype), the prevalence of having any HFE gene mutation is around 46% in the Mediterranean population [ 34 , 60 ], which turn it into an important risk factor to consider when prescribing iron supplementation. There are some indications from observational studies that not only iron deficiency but also iron excess negatively affects the child’s neurodevelopment [ 18 , 32 , 33 , 35 , 36 ] and, based on that, some main researchers in this field have proposed to adapt the prenatal iron supplementation to the individual’s requirements to mitigate the potential damage from any maternal iron imbalance [ 22 , 23 , 25 , 41 ]. However, few studies have tested this hypothesis, obtaining inconsistent results [ 37 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is important to highlight that the overall prevalence of HFE gene alterations in our population is quite high [ 34 ]. After some authors have concluded that both iron deficit and excess may injure the child’s cognitive and motor development [ 32 , 35 , 36 ], they advise that prenatal iron supplementation should be individualized considering maternal iron stores, as well as other lifestyle and biological conditions [ 37 , 38 ]. We supported this advice after having shown by a community-based Randomized Clinical Trial (RCT) the effectiveness of adapting iron doses to maternal haemoglobin (Hb) levels early in pregnancy in preventing iron deficiency, anaemia, and haemoconcentration [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum ferritin was measured by an electrochemiluminescence immunoassay (ECLIA) on the Cobas e411 analyser (Roche, Almere, The Netherlands). Based on the most commonly applied definitions during pregnancy, iron deficiency was defined as ferritin <15 μg/l and iron overload as ferritin >150 μg/l ( 3 , 18 , 19 ) . Ferritin is a positive acute-phase protein, that is elevated in the presence of infection or inflammation, regardless of iron status ( 20 , 21 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Maternal ID with or without anaemia during pregnancy is reported to negatively affect the mother and the foetus/newborn [ 3 , 4 ]. Mothers with ID often experience increased levels of fatigue and reduced physical and mental performance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%